Multicultural Values and Identity of Students through the Bhineka Edu Cultural Learning Platform: James A. Banks Perspective on Character Education - Siti Hawa; Dinie Anggraeni Dewi; Yeni Yuniarti; Nissa Aulia Belistiana Utami (Universitas Pendidikan Ganesha, 2026)
Indonesia’s cultural diversity is essential for developing multicultural character from elementary school. However, digital technology has not been optimally used to contextualize character education. This reflects the limited availability of integrative multicultural learning media. This study aims to analyze the role of the Bhineka Edu cultural learning platform in supporting the internalization of multicultural character values among elementary school students. This study employed a qualitative approach using a case study design. The research participants consisted of teachers and elementary school students who utilized Bhineka Edu in thematic learning and Pancasila Education focusing on cultural diversity topics. Data were collected through classroom observations, visual documentation of the platform and learning activities, and field notes. The data were analyzed thematically through data reduction, data display, and conclusion drawing, with data validity ensured through source and technique triangulation. The findings reveal that Bhineka Edu presents Indonesian culture comprehensively through features on traditional clothing, traditional houses, traditional weapons, local foods, as well as traditional games and sports supported by interactive visualizations. The implementation of the platform promotes active student engagement, facilitates reflective classroom discussions, and fosters values of tolerance, empathy, togetherness, sportsmanship, and national identity. This study concludes that Bhineka Edu functions as an effective pedagogical medium for strengthening multicultural character education in elementary schools.